KAJIAN TOKOH ISLAM MODERN MUHAMMAD ABDUH - Durotul Qoyimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Muhammad Abduh, a prominent Islamic modernist, is renowned for his contributions to establishing a rational, progressive, and contextual Islamic paradigm. Through his rich intellectual journey, Abduh offered solutions to the stagnation of Islamic thought through the renewal of education, Islamic law, and an emphasis on reason, ijtihad, and the integration of religious and scientific knowledge. His works, such as Tafsir al-Manar and Risalah al-Tawhid, inspired reform movements in the Islamic world, including Indonesia. Abduh's thought, encompassing education, knowledge, politics, and theology, remains relevant in addressing the challenges of globalization, particularly in shaping a moderate and forward-thinking Islamic education. Abduh's educational reforms at Al-Azhar, his emphasis on rationality and ijtihad, and his ideas on human freedom and consultative governance, serve as important foundations for the modernization of Islam.